FRI0365 Factors associated with left ventricular diastolic dysfunction in patients with systemic lupus erythematosus. (12th June 2018) - Baek, I.-W.; Kim, K.-J.; Park, Y.-J.; Kim, W.-U.; Cho, C.-S.
Abstract : Objectives: Myocardial damage is common and often silent in patients with systemic lupus erythematosus (SLE). In this study, we investigated the clinical parameters associated with left ventricular diastolic dysfunction in SLE patients using algorithms of 2016 American Society of Echocardiography/European Association of Cardiovascular Imaging (ASE/EACVI) recommendations. Methods: Sixty consecutive SLE patients and 38 controls matched for age and sex who were free of clinical cardiovascular disease were enrolled. Left ventricular diastolic dysfunction was assessed by echocardiography using 2016 ASE/EACVI guidelines. The demographic, clinical and laboratory data were obtained from medical records. Results: Diastolic dysfunction was more common in SLE patients compared with controls (38.3% versus 13.2%, p=0.011), while LV ejection fraction was not different between groups. When patients were divided into 2 groups according to the presence of diastolic dysfunction, patients with diastolic dysfunction had higher prevalence of hypertension (p<0.001), dyslipidemia (p=0.031) and chronic kidney disease (p=0.045), but there was no difference between groups with regard to other organ involvement or autoantibody profile. Importantly, patients with diastolic dysfunction showed significantly higher SLICC/ACR damage index (p=0.001) and C-reactive protein levels (p=0.005). In multivariate regression analysis, hypertension (OR=16.6. 95% CI=3.466–79.479, p<0.001), higher SLICC/ACR damage index (OR=1.68, 95% CI=1.039–2.720, p=0.034), and CRP level (OR=1.12, 95% CI=1.004–1.254, p=0.042) was independently associated with diastolic dysfunction in SLE patients Conclusions: Diastolic dysfunction is more common in SLE patients, and overall inflammatory burden reflected by SLICC/ACR damage index as well as conventional cardiovascular risk factors are associated with development of diastolic dysfunction in SLE patients. Disclosure of Interest: None declared